Investigating the impact of bridging the digital divide on reducing unemployment and achieving SDGs in Saudi Arabia: Panel ARDL approach - Ali, Mohamed Ali; Tayfor, Abdelsamie Eltayeb; Alawad, Ayman Abdelghani; Lefkir, Hamza; KNOUCH, Mohamed (Asian Economic and Financial Review, 2025)
This study seeks to examine how Internet penetration and usage affect the unemployment rate among Saudis by gender. A descriptive analysis was used to generate two standard models and conduct an analysis on them using the ARDL Approach. The findings reveal that there is a statistically significant relationship between the independent variables in the model developed, which are "Internet penetration rate" and "male Internet use," and the dependent variable "male unemployment rate." Additionally, there is a relationship between the independent variables "Internet penetration rate" and "female Internet use" and the dependent variable "female unemployment rate." In addition, the findings indicated that bridging the digital gap will help reduce unemployment and attain the sustainable development goals in the Kingdom of Saudi Arabia. Policymakers should focus on the expansion of Internet coverage, upgrading digital skills, e-employment, enhancement of digital infrastructures for SMEs, and aligning digital inclusion strategies with Vision 2030 and the UN SDGs to reduce the digital divide, tackle unemployment, and contribute to further sustainable economic development. This study adds to the existing literature by taking a closer look at how Internet penetration and usage affect unemployment rates in Saudis by gender and shows that this can reduce unemployment through bridging the digital divide and subsequently support advancing toward the SDGs.